Befores & Afters Magazine - Failes, Ian, ....- (S.l. : s.n., 2022)
Inside issue #2 of befores & afters magazine: – 3D scanning rigs – Wireframes – Virtual production terminology – DIY FX – Motion bases
Keywords: Animation; Visual effects